Fuzzy homotopy continuation method for solving fuzzy nonlinear equations - Nor Hasyimah Abdul Razak (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2014)
In this dissertaion, a method known as Fuzzy Homotopy Continuation has been developed to solve fuzzy nonlinear equation. This method is develop based on the extended classical Homotopy Continuation Method. Fuzzy Homotopy Continuation Method involves numerically finding the solution of a problem by starting from the solution of a known problem and continuing the solution until the known problem is homotoped to the given problem.